2020
DOI: 10.1242/dev.190678
|View full text |Cite
|
Sign up to set email alerts
|

The Gridlock transcriptional repressor impedes vertebrate heart regeneration by restricting expression of lysine methyltransferase

Abstract: Teleost zebrafish and neonatal mammalian hearts exhibit the remarkable capacity to regenerate through dedifferentiation and proliferation of pre-existing cardiomyocytes (CMs). Although many mitogenic signals that stimulate zebrafish heart regeneration have been identified, transcriptional programs that restrain injury-induced CM renewal are incompletely understood. Here, we report that mutations in gridlock (grl; also known as hey2), encoding a Hairy-related basic helix-loop-helix transcriptional repressor, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…SMYD2 (SET [suppressor of variegation, enhancer of zeste, trithorax] and MYND [myeloid-nervy-DEAF1] domain-containing protein 2; histone lysine methyltransferase) is robustly expressed in neonatal heart and regulates cardiac development and regeneration. 37,38 Similar to TBX5 (t-box transcription factor 5), we also found that its promoter interacted with an activated enhancer embedded in its 3rd intron in DCM hearts (Figure 3F). Other DCM-enriched E-P examples ( MEF2D [myocyte enhancer factor 2d], regulator for myogenesis 39 and cardiac stress 40 ; MYPN [myopalladin], regulator for maintaining sarcomeric integrity 41 ) are displayed in Figure S4F and S4G, respectively.…”
Section: Resultsmentioning
confidence: 62%
“…SMYD2 (SET [suppressor of variegation, enhancer of zeste, trithorax] and MYND [myeloid-nervy-DEAF1] domain-containing protein 2; histone lysine methyltransferase) is robustly expressed in neonatal heart and regulates cardiac development and regeneration. 37,38 Similar to TBX5 (t-box transcription factor 5), we also found that its promoter interacted with an activated enhancer embedded in its 3rd intron in DCM hearts (Figure 3F). Other DCM-enriched E-P examples ( MEF2D [myocyte enhancer factor 2d], regulator for myogenesis 39 and cardiac stress 40 ; MYPN [myopalladin], regulator for maintaining sarcomeric integrity 41 ) are displayed in Figure S4F and S4G, respectively.…”
Section: Resultsmentioning
confidence: 62%
“…1 G-J). Semi-qualitative analysis of the fibrotic area was performed to indicate the increased severity of the damage as shown in previous studies ( Bise et al, 2020 ; She et al, 2020 ; Sun et al, 2022 ; Xia et al, 2022 ). Acid fuchsin orange G (AFOG) staining revealed fibrotic tissue in foxm1 m/m ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For PCNA staining, adult zebrafish hearts were extracted and fixed in 4% paraformaldehyde for 1 h at room temperature, and subsequently dehydrated in 30% sucrose, then embedded in OCT solution and further sectioned at 10 μm thickness with a Leica cryostat. Immunostaining on cryosections was performed as previously described [ 14 ], administrated with antigen retrieval at 98 °C for 20 min in the citric acid buffer. CM proliferation index was calculated as the number of PCNA + Mef2C + cells over the number of total Mef2C + cells.…”
Section: Methodsmentioning
confidence: 99%